Pathway Complexity in Supramolecular Polymerization of Porphyrin Dyads for Kinetic Control of Helicity - Hosoowi Lee; Yongho Lee; Minhyeong Lee; Dae Eun Kang; Jiwon Kim; Dong Ha Kim; Woo‐Dong Jang (Aggregate)
ABSTRACT The supramolecular polymerization of porphyrin dyad (PD) shows the pathway complexity leading to the formation of kinetically metastable nanoparticles (PDParticle) through rapid cooling and thermodynamically stable fibrous supramolecular polymers (PDFiber) through slow cooling. The kinetically metastable PDParticle is gradually transformed to the thermodynamically stable PDFiber. Due to the inherent achirality of PD, AFM images exhibited a random distribution of both M and P helices. Introducing chiral alkyl chains achieved a predominant helicity in PDFiber, with (S)‐PD favoring M helices and (R)‐PD favoring P helices. The addition of chiral 2‐methyl pyrrolidine (MePy) further influences this transformation by retarding the transition from PDParticle to PDFiber through axial coordination with the zinc porphyrin units, affecting the helicity of the resulting supramolecular polymer. By manipulating the cooling rates and environmental conditions, we demonstrate the reversible control over circular dichroism (CD) and circularly polarized luminescence (CPL), providing insight into the relationship between structural chirality and optical activity.